Exploring resilience among Palestinian hospital nurses: A phenomenological study (Journal of Health Sciences, 2025)
Introduction: Nurses play a vital role in the Palestinian healthcare system and work in challenging environments. Their well-being and providing high-quality care can be affected by multiple stressors. Resilience among nurses is essential for sustaining an effective workforce. This study explores sources of resilience among nurses working in the hospitals in Nablus, northern West Bank, Palestine.Methods: A qualitative phenomenological approach was used. Purposeful sampling selected three hospitals (one governmental, one private, and one non-profit). Three focus group discussions were conducted with 24 full-time hospital nurses between October and December 2018. Group discussions were held in Arabic, then transcribed to paper then inductive thematic analysis done, and finally, the themes and sub-themes translated in English by a certified translator.Results: Analysis yielded four main themes and eight sub-themes: Patriotic values and beliefs; motivation; coping skills; and supportive relationships.Conclusions: Understanding nurses’ sources of resilience can inform interventions to support their well-being and capacity to face adversity. Further research is recommended to examine changes over time and in other regions of Palestine.